2020
DOI: 10.1002/sdtp.13748
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of 520nm Laser Diode Underwater Wireless Optical Communication Systems in the Presence of Oceanic Turbulence

Abstract: To promote the application of the underwater wireless optical communication (UWOC) system in the ocean, we investigated the performance of the 520nm laser diode UWOC system in the presence of oceanic turbulence. In this paper, we analyzed the performance of the UWOC system under the pure water, 4.17g/L salinity water and 35.42g/L salinity water conditions, and preliminarily demonstrated the effect of the salinity‐induced oceanic turbulence on the UWOC system. The experimental results have potential value for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…For instance, the Weibull model was used to characterize the fading of salinity-induced turbulence in UWOC channels [26], and generalized gamma and exponentiated Weibull distributions were found to model the fading statistics perfectly [27]. Previous studies have shown that uniform saline channels induce greater turbulence when subjected to turbulent flow due to the faster variations in the refractive index along the optical path [13].…”
mentioning
confidence: 99%
“…For instance, the Weibull model was used to characterize the fading of salinity-induced turbulence in UWOC channels [26], and generalized gamma and exponentiated Weibull distributions were found to model the fading statistics perfectly [27]. Previous studies have shown that uniform saline channels induce greater turbulence when subjected to turbulent flow due to the faster variations in the refractive index along the optical path [13].…”
mentioning
confidence: 99%
“…As being improving the system capacity and essential assets of high data rate underwater wireless communication technology, optical communication towards 5G is the key solution that attracts the scientific community. Although, the most recent experimental study and the performance evaluation of 520nm wavelength laserdiode towards 5G is presented as [310]. In [310], the authors have analyzed the performance of an underwater optical system under consideration of varying salinity conditions in pure water.…”
Section: A 5g Networking System In Underwatermentioning
confidence: 99%
“…Although, the most recent experimental study and the performance evaluation of 520nm wavelength laserdiode towards 5G is presented as [310]. In [310], the authors have analyzed the performance of an underwater optical system under consideration of varying salinity conditions in pure water. Facing these issues, the Generalized Frequency Division Multiplexing (GFDM) is proposed as a novel underwater wireless network candidate towards the next generation standard based on multi-branch multicarrier filter bank in [44].…”
Section: A 5g Networking System In Underwatermentioning
confidence: 99%